2020
DOI: 10.1111/eva.12959
|View full text |Cite
|
Sign up to set email alerts
|

Rapid adaptation (or not) in restored plant populations

Abstract: Mismatches between the traits of a colonizing population and a novel habitat can generate strong selection, potentially resulting in rapid adaptation. However, for most colonization events, it can be difficult to detect rapid adaptation or distinguish it from nonadaptive evolutionary changes. Here, I take advantage of a replicated prairie restoration experiment to compare recently established plant populations in two closely located restored prairies to each other and to their shared source population to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 71 publications
(86 reference statements)
2
12
0
Order By: Relevance
“…A common garden experiment revealed that these differences are partly heritable and likely adaptive, indicating adaptive evolution. Evolution in restoration was documented previously in two annual species (Kulpa & Leger, 2013;Magnoli, 2020). We bring further evidence for two perennials, suggesting that evolution in restoration is probably rather common.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A common garden experiment revealed that these differences are partly heritable and likely adaptive, indicating adaptive evolution. Evolution in restoration was documented previously in two annual species (Kulpa & Leger, 2013;Magnoli, 2020). We bring further evidence for two perennials, suggesting that evolution in restoration is probably rather common.…”
Section: Discussionsupporting
confidence: 81%
“…In the context of ecological restoration, first studies suggest that selection pressures at restoration sites can alter heritable phenotypic distribution of seeded species. Specifically, Kulpa & Leger (2013) detected strong selection towards smaller plant and seed size and earlier flowering in an annual grass, and Magnoli (2020) and Magnoli & Lau (2020) showed partly adaptive trait differentiation in an annual legume after seeding the same batch of seed to two restored sites. Yet, these studies focused on a single annual species each.…”
Section: Introductionmentioning
confidence: 98%
“…Plants grown at the Marshall site had very low fitness compared to those grown at the Lux site, with many families not producing any seeds (Appendix : Fig. S2), due to both high mortality and low seed production of surviving plants (Magnoli, in press ). Selection did not significantly differ between sites for any trait (site × trait interactions, all P > 0.18; Appendix : Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, we may find evidence of past selection in one population but not the other not because of differences in selection pressures, but because of differences in the populations’ capacities to respond to selection. The two populations may differ in their capacities to adapt due to differences in population size; the Marshall population has been consistently smaller than the Lux population since initial establishment (Magnoli, in press ). Smaller population size may lead to lower genetic diversity (Leimu et al 2006), which may mean that the Marshall population is less able to respond to selection than the larger, more genetically diverse Lux population.…”
Section: Discussionmentioning
confidence: 99%
“…Silliman et al 2018, Magnoli 2020 al. 2021 Piece loss (extinction) Successful 6 Cione et al 2002, Warren et al 2003*, Redi et al 2005, Sutton 2015, Brown et al 2016, Moyer and Brewer 2018.…”
mentioning
confidence: 99%